Resource Optimization Model to Increase Efficiency in Aircraft Maintenance Operations, Using Lean Six Sigma and Linear Programming - Rojas-Delgado, Natalia (2022)
In the last 10 years, the aeronautical sector has experienced a high impact growth worldwide. This directly affects the growth and development of aeronautical maintenance due to the increase in aircraft purchases. For this reason, Certified Repair Stations play an important role in this current high demanded sector. This research aims to increase the efficiency of aircraft maintenance operations in a certified repair station. Currently, the efficiency level is 77.18% and is below 95% recommended for this sector. This negatively affects the economic situation of the company since in the period from 2018 to 2020, 39 work orders were not attended, which represents 14% of the total turnover. For this reason, a resource optimization model has been designed using the Lean Six Sigma methodology under the DMAIC tool, to run the linear programming using Lingo subsequently. After the simulation, efficiency reaches 100%, which is within the range established by aeronautical standards; likewise, delay costs decrease by 100%. Finally, it is expected that the model described above can be applied in certified repair stations with similar problems.